Aurora kinase A is essential for meiosis in mouse oocytes - Blengini, Cecilia S; Ibrahimian, Patricia; Vaskovicova, Michaela; Drutovic, David; Solc, Petr; Schindler, Karen (PLoS genetics, 2021)
The Aurora protein kinases are well-established regulators of spindle building and chromosome segregation in mitotic and meiotic cells. In mouse oocytes, there is significant Aurora kinase A (AURKA) compensatory abilities when the other Aurora kinase homologs are deleted. Whether the other homologs, AURKB or AURKC can compensate for loss of AURKA is not known. Using a conditional mouse oocyte knockout model, we demonstrate that this compensation is not reciprocal because female oocyte-specific knockout mice are sterile, and their oocytes fail to complete meiosis I. In determining AURKA-specific functions, we demonstrate that its first meiotic requirement is to activate Polo-like kinase 1 at acentriolar microtubule organizing centers (aMTOCs; meiotic spindle poles). This activation induces fragmentation of the aMTOCs, a step essential for building a bipolar spindle. We also show that AURKA is required for regulating localization of TACC3, another protein required for spindle building. We conclude that AURKA has multiple functions essential to completing MI that are distinct from AURKB and AURKC.
Keywords: Aurora Kinase B; Cell Nucleus Division; meióza; fetální proteiny; vývojová regulace genové exprese; Microtubule-Organizing Center; Aurora Kinase A; protein-serin-threoninkinasy; Proto-Oncogene Proteins; aurora kinasa B; organizační centrum mikrotubulů; Mice; Spindle Apparatus; Microtubule-Associated Proteins; Cell Cycle Proteins; proteiny asociované s mikrotubuly; aparát dělícího vřeténka; Gene Expression Regulation, Developmental; Protein Serine-Threonine Kinases; aurora kinasa C; Oocytes; Chromosome Segregation; proteiny buněčného cyklu; póly dělícího vřeténka; ženské pohlaví; zvířata; oocyty; Humans; Meiosis; segregace chromozomů; Aurora Kinase C; protoonkogenní proteiny; myši; Fetal Proteins; aurora kinasa A; Female; dělení bunečného jádra; lidé; Spindle Poles; Animals